Superior mesenteric artery syndrome with superior mesenteric artery thrombosis: A case report - Seçkin, Erdi (Journal of Surgery and Medicine, 2019)
Superior mesenteric artery (SMA) syndrome is a rare syndrome with symptoms including nausea, vomiting and epigastric pain. SMA syndrome is also known as Wilkie’s syndrome, mesenteric root syndrome, chronic duodenal ileus syndrome. SMA syndrome is vascular compression of the third part of the duodenum between the SMA and the aorta. In this article, we will present an adult patient with SMA syndrome who was admitted to the emergency service with abdominal pain and associated thrombosis of her superior mesenteric artery, demonstrated by computed tomography. Since SMA syndrome is rare and symptoms are not frequent, some diagnostic difficulties might happen and this will lead unnecessary long-term symptomatic treatments for the patient. In such patients, mesenteric artery thrombosis should be considered in differential diagnosis of abdominal pain.